Adjuvant Radiotherapy and/or Chemotherapy for Endometrial Cancer, Status as at 2019: Opinion of the Uterus Commission of the Gynecological Oncology Working Group (AGO) - Emons, Günter (Geburtshilfe Frauenheilkd, 2019)
The role of adjuvant radiotherapy and/or chemotherapy in the primary treatment of endometrial cancer with a high risk of recurrence has still not been conclusively determined. The results of 3 large randomized controlled studies on different aspects of this issue have been published in full in recent months, and the relevant results are analyzed here.